An Indwelling Urethral Catheter Knotted Around a Double-J Ureteral Stent: An Unusual Complication after Kidney Transplantation - E. G. Warmerdam; R. J. Toorop; A. C. Abrahams; P. Berger (Case Reports in Nephrology)
Urethral catheterization is a common procedure with a relatively low complication rate. Knotting of an indwelling urethral catheter is a very rare complication, and there are only a few case reports on knotted catheters, most of them concerning children. We report an especially rare case where a urethral catheter formed a knot around a double-J ureteral stent after a kidney transplantation. We will discuss the various risk factors for knotting of a catheter and the methods to untangle a knot.